2019
DOI: 10.33736/jaspe.1349.2019
|View full text |Cite
|
Sign up to set email alerts
|

Phytoremediation of Palm Oil Mill Effluent (POME) Using Eichhornia crassipes

Abstract: It is inevitable that the manufacturing process of palm oil is accompanied by the generation of a massive amount of high strength wastewater, namely palm oil mill effluent (POME), which could pose serious threat to the aquatic environment. POME which contains high organic compounds originating from biodegradable materials causes water pollution if not properly managed. Palm oil industries are facing the challenges to make ends meet in the aspects of natural assurance, financial reasonability and development su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 50 publications
1
3
0
4
Order By: Relevance
“…Microbes such as bacteria are accountable for decaying biological matter (Farhadkhani et al, 2018). The present study was confirmed by Wei (2019) who reported efficient removal of BOD (92.78%) in the phytotreatment of palm oil mill wastewater for 21 days of holding time using water hyacinth. The COD examination is frequently used in combination with the BOD test to assess the quantity of nonbiodegradable organic material in the wastewater.…”
Section: Removal Of Chemical Parameters Of Pme By P Stratiotessupporting
confidence: 81%
“…Microbes such as bacteria are accountable for decaying biological matter (Farhadkhani et al, 2018). The present study was confirmed by Wei (2019) who reported efficient removal of BOD (92.78%) in the phytotreatment of palm oil mill wastewater for 21 days of holding time using water hyacinth. The COD examination is frequently used in combination with the BOD test to assess the quantity of nonbiodegradable organic material in the wastewater.…”
Section: Removal Of Chemical Parameters Of Pme By P Stratiotessupporting
confidence: 81%
“…WH was employed to repair cyanide pollution in the waste water of a steel factory, and the result showed 95% was removed within 3 d [ 82 ]. Moreover, WH has also been reported to repair the soil pollution of oil and palm oil plants containing palm oil plants [ 63 , 64 ].…”
Section: Applications Of Wh In Maintaining Environmental Sustainabilitymentioning
confidence: 99%
“…Banyaknya cairan yang dihasilkan terutama berasal dari proses sterilisasi, klarifikasi, proses hydrocyclone untuk pemisahan kulit dan inti sawit (Wei et al, 2019). Apabila tidak dikelola secara baik, limbah cair kelapa sawit berpotensi menimbulkan efek negatif terhadap komunitas fitoplankton di perairan.…”
unclassified
“…Saat ini, telah banyak penelitian fitoremediasi LCKS yang telah dilaporkan. Beberapa tumbuhan yang telah diteliti mampu meremediasi LCKS adalah Scirpus grossus (Sa'at et al, 2022), Cyperus alternifolius (Sa'at et al, 2019), Eichhornia crassipes (Wei et al, 2019) dan Ipomoea aquatica atau dikenal dengan kangkung air (Zulfahmi et al, 2021).…”
unclassified